Application of flow control using plasma actuator to horizontal axis wind turbine. Issue 5 (September 2020) - Matsuda, T; Maeda, T; Kamada, Y; Ushigusa, T; Kobayashi, H; Tanaka, M
Abstract: In this study, the clarification of the effect of plasma flow control on the rotor performance was carried out as a wind turbine control technology. The flow fields around rotor and the loads acting on wind turbine were measured by wind tunnel test using a test wind turbine with plasma actuator. As a result, in the low tip speed ratio, the power coefficient of Plasma On is larger than that of Plasma Off and the thrust coefficient of Plasma On slightly increased. In particular, the remarkable increase in the power coefficient was 24% at the most effective tip speed ratio. The wind turbine thrust increased slightly in the low tip speed ratio regime, but was less affected by the plasma flow control. In addition, when the power coefficient and thrust coefficient were calculated using the velocity components of the flow field around the wind turbine, the same tendency as in the wind turbine performance test was shown.